The role of Court of Auditors and Legal Auditor in reducing financial corruption in public and private companies (Field study) - SEFFAHLOU Rachid (Journal of North African Economies, 2025)
This study aims to highlight the aspects and forms of financial corruption and its effects on public institutions and public and private economic companies, and to clarify the laws and organizations developed to combat it. To achieve the objectives of the study, the descriptive approach was used in the theoretical aspect, and a questionnaire was designed and distributed to actors in the field of public accounting and auditing, as the study sample included 62 individuals. The study concluded that financial corruption does not occur in institutions except in a collusive manner between several individuals and it is discovered only by specialists, and the Court of Auditors is considered an effective tool for preserving public money in non-profit public institutions and organizations, especially after expanding its supervisory powers and areas of intervention, while the legal auditor is considered an auxiliary of justice in economic enterprises, because he is obligated to declare to the public prosecutor the misdemeanor acts he discovers While performing his duties, and thus contributes to limiting the spread of the crime of financial corruption in companies and organizations he controls.